Anion photoelectron spectroscopy and density functional theory study of TM2Sin− (TM = V, Cr; n = 14–20) clusters. Issue 30 (26th July 2022) - Wang, Kai; Yin, Guang-Jia; Jia, Ze-Zhao; Miao, Lin; Moro, Ramiro; von Issendorff, Bernd; Ma, Lei
Abstract : We investigated the structural evolution and electronic properties of medium-sized silicon cluster anions doped with two transition metal atoms, TM2 Si n − (TM = V, Cr; n = 14–20), by using mass-selective anion photoelectron spectroscopy combined with density functional theory (DFT) calculations. Abstract : We investigated the structural evolution and electronic properties of medium-sized silicon cluster anions doped with two transition metal atoms, TM2 Si n − (TM = V, Cr; n = 14–20), by using mass-selective anion photoelectron spectroscopy combined with density functional theory (DFT) calculations. Putative ground state structures of these clusters were obtained by using a genetic algorithm coupled with the DFT calculations. It was found that the two TM atoms tend to form a TM–TM bond, which – except for V2 Si19 − – is shorter than the nearest neighbour distance in the crystalline state of the respective metals. The V2 Si n − clusters with n = 14 to 17 exhibit structures based on a silicon hexagonal antiprism, while the larger ones exhibit more fullerene-like cage structures. Cr2 Si n − clusters follow the same trend, although with a silicon hexagonal prism structure for n = 14 and 15, and the transition to fullerene-like structures occurring at n = 17. Among these clusters, TM2 Si18 − have the largest average binding energy and second order differences in energy, therefore the highest relative stability. All of the clusters possess total magnetic moment of 1 μB, but with very different contributions from the doped TM atoms. Especially in the Cr doped clusters there is a tendency towards an anitiferromagnetic arrangement of the magnetic moments of the two Cr atoms.